Fatigue analysis of 100 meters all-out front crawl using surface EMG - Stirn, I.; Jarm, T.; Kapus, V.; Strojnik, V. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of the study was to estimate fatigue in arm propelling muscles by analyzing electromyographic (EMG) signal. Eleven male competitive swimmers performed a 100 meters all-out front crawl. Trials were recorded to obtain kinematical data, lactate concentration after the swims were measured. EMG signals of latissimus dorsi (LD), pectoralis major (PM) and triceps brachii (TB) were recorded, also. Average lactate concentration was 14.1 ± 2.93 mmol.l-1. Stroke length, stroke rate and swimming speed decreased. The EMG amplitude (ARV) for the lower part of LD and for TB increased and the mean frequency (MNF) decreased for 20.5 ± 9.1 to 24.6 ± 8.4 % for all muscles under observation (P<0.05). No differences in relative MNF decrease between the muscles were found. The progression of fatigue monitored by the surface EMG parameters during swimming was clearly shown.